Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.
Upcoming SlideShare
×

# Integrated 2 Section 3-1

494 views

Published on

Equations and Formulas

Published in: Education, Technology
• Full Name
Comment goes here.

Are you sure you want to Yes No
Your message goes here
• Be the first to comment

• Be the first to like this

### Integrated 2 Section 3-1

1. 1. Chapter 3 Equations and Inequalities
2. 2. Section 3-1 Equations and Formulas
3. 3. Essential Questions ✤ How do you determine if a number is a solution of an equation? ✤ How do you solve an equation or a formula? ✤ Where you’ll see it: ✤ Travel, safety, physics
4. 4. Vocabulary 1. Equation: 2. True Equation: 3. False Equation: 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
5. 5. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: 3. False Equation: 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
6. 6. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
7. 7. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
8. 8. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: An equation with a variable 5. Solution of the Equation: 6. Solve an Equation:
9. 9. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: An equation with a variable 5. Solution of the Equation: The value that makes the equation true 6. Solve an Equation:
10. 10. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: An equation with a variable 5. Solution of the Equation: The value that makes the equation true 6. Solve an Equation: Find the values that make it true by isolating the variable
11. 11. Formula
12. 12. Formula An equation (rule) that states a relationship between two or more quantities
13. 13. Formula An equation (rule) that states a relationship between two or more quantities We can solve for any part of a formula!!!
14. 14. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5
15. 15. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x
16. 16. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x
17. 17. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x
18. 18. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7
19. 19. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3
20. 20. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4
21. 21. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2
22. 22. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2 x=2
23. 23. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2 x=2 14(2) + 3 = 12(2) + 7
24. 24. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2 x=2 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
25. 25. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 2 2 x=2 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
26. 26. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 x=2 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
27. 27. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
28. 28. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
29. 29. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
30. 30. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
31. 31. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
32. 32. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 x = −1 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
33. 33. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 x = −1 2 2 2 x=2 3 =9 3(−1) + 8 = 5 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
34. 34. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 x = −1 2 2 2 x=2 3 =9 3(−1) + 8 = 5 2 (−3) = 9 −3 + 8 = 5 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
35. 35. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23
36. 36. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3
37. 37. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 b = 17
38. 38. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 b = 17 17 − 3 = 14
39. 39. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 17 − 3 = 14
40. 40. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 1 m= 5 17 − 3 = 14
41. 41. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 1 m= 5 17 − 3 = 14 1 (45) = 9 5
42. 42. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 1 m= 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
43. 43. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 m= 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
44. 44. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
45. 45. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
46. 46. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 w=4 1 (45) = 9 5 45 =9 5
47. 47. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 w=4 1 (45) = 9 5 4(4) + 7 = 23 45 =9 5
48. 48. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 w=4 1 (45) = 9 5 4(4) + 7 = 23 45 16 + 7 = 23 =9 5
49. 49. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101
50. 50. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation
51. 51. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6
52. 52. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x −3x
53. 53. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5
54. 54. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5
55. 55. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1
56. 56. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1 Check!
57. 57. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1 Check!
58. 58. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1 Check!
59. 59. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 x=1 Check!
60. 60. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 Check!
61. 61. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 18 18 Check!
62. 62. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 18 18 Check! a=6
63. 63. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 18 18 Check! a=6 Check!
64. 64. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40
65. 65. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated
66. 66. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42
67. 67. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6
68. 68. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6 x−5=7
69. 69. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6 x−5=7 +5 +5
70. 70. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6 x−5=7 +5 +5 x = 12
71. 71. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 6(x − 5) = 42 6 6 x−5=7 +5 +5 x = 12
72. 72. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 6 6 x−5=7 +5 +5 x = 12
73. 73. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 x−5=7 +5 +5 x = 12
74. 74. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 7g = −28 x−5=7 +5 +5 x = 12
75. 75. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 7g = −28 x−5=7 7 7 +5 +5 x = 12
76. 76. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 7g = −28 x−5=7 7 7 +5 +5 x = 12 g = −4
77. 77. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5
78. 78. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5
79. 79. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5 F = 77.4 + 32
80. 80. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5 F = 77.4 + 32 F = 109.4
81. 81. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5 F = 77.4 + 32 F = 109.4 43°C is 109.4°F
82. 82. Homework
83. 83. Homework p. 106 #1-9 all, 11-37 odd “The greatest challenge to any thinker is stating the problem in a way that will allow a solution.” - Bertrand Russell